MODIFIKASI PISAU MESIN PENEPUNG ATC DENGAN GARIS MATA POTONG PADA SUDUT 33O ARAH RADIAL - Nuha Desi Anggraeni (Machine : Jurnal Teknik Mesin, 2020)
Kappa carrageenan is a hydrocolloid compound which is extracted from the red seaweed species of Eucheuma Cottonii. Kappa Carrageenan is widely used in the food processing industry as a thickener, stabilizer and emulsifier. ATC (Alkali Treated Cottonii) which is the intermediate product to obtain SRC (Semi-Refined Carrageenan) will go through further processing, such as chopping and grinding. This research is a continuation of the research undertaken to develop ATC grinding machines. This research is focused on modifying the geometry of grinding tools to obtain finer powder results than former research. The tests that have been performed show that the modifications of tool geometry provide better results, which is able to achieve fine powder up to 100 mesh. But the capacity of this grinding machine is not quite satisfactory because the amount of flour reaches 100 mesh is only 9 grams from 50 grams input.